Against time: preliminary notes to an anarchic epistemology of times. (3rd July 2018) - Fine, David
ABSTRACT: This paper questions the view that time, even as a concept, is fundamentally singular, universal and all-embracing. Instead it adopts then abandons a phenomenological approach to propose that there are any number or indeterminate sets of times, which in their turn cannot be collapsed into a coherently unified account of time. This thesis is backed up by a suite of three examples to indicate that when deployed as a means of archaeological enquiry, the acknowledgement of limitless types of time possesses the potential to reach realms of knowledge otherwise not obtainable through the examination of material remains.